PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN LKPD DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SISWA KELAS VI SD - Diah Juhaeriah; Sholeh Hidayat; Ajat Sudrajat (Jurnal Muara Pendidikan, 2021)
The purpose of this research is to analyze the effect of using problem based learning model assisted by LKPD and the ability to think critically on the ability to solve math problems of grade VI at elementary school students. This research uses an experimental method with a 2 2 factorial design. The population are of the sixth grade students of SDN Sangiang 2 totaling 60 students, the sample was taken using random techniques totaling 30 students. The data collection technique used a test in the form of description questions. The data analysis technique used statistical analysis with two-way ANOVA technique. Based on the calculation results of the research are us follows: (1) the existence of solution to solve mathematical problems between students who are taught using a problem based learning models assisted by LKPD and without the assistance of LKPD, (2) the interaction of the problem based learning model assisted by LKPD and without LKPD and thinking skills critical to ability to solve math problems of class VI SD,(3) there are differences in mathematics learning outcomes in the form of the ability to solve mathematical problems between students who have high critical thinking skills who are taught using problem based learning models using LKPD, and (4) there are differences in mathematics learning outcomes in the form of the ability to solve mathematical problems between students who have low critical thinking skills who are taught using problem based learning models using LKPD. The abundance of this research is to state that there is an effect of problem based learning models and critical thinking skills on the ability to solve math problems of grade VI elementary school students.